2014
DOI: 10.1302/0301-620x.96b5.32516
|View full text |Cite
|
Sign up to set email alerts
|

Functional outcome and alignment in computer-assisted and conventionally operated total knee replacements

Abstract: We performed a randomised controlled trial comparing computer-assisted surgery (CAS) with conventional surgery (CONV) in total knee replacement (TKR). Between 2009 and 2011 a total of 192 patients with a mean age of 68 years (55 to 85) with osteoarthritis or arthritic disease of the knee were recruited from four Norwegian hospitals. At three months follow-up, functional results were marginally better for the CAS group. Mean differences (MD) in favour of CAS were found for the Knee Society function score (MD: 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
42
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(51 citation statements)
references
References 35 publications
8
42
1
Order By: Relevance
“…Our times were recorded from first-skin incision to completion of closure of the wound (skin-to-skin) to give a measure of the actual time the operation takes. The mean “skin-to-skin” time of 72 minutes seen in this study is virtually identical to recent studies comparing conventional and patient specific jigs, which are claimed to have shorter operating times [7] and much shorter than times quoted for other recent navigation series [3], [7], [17]. In our institution, with the use of navigation routinely, operation times appear to still be within the range that would be expected for non-navigated surgery.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Our times were recorded from first-skin incision to completion of closure of the wound (skin-to-skin) to give a measure of the actual time the operation takes. The mean “skin-to-skin” time of 72 minutes seen in this study is virtually identical to recent studies comparing conventional and patient specific jigs, which are claimed to have shorter operating times [7] and much shorter than times quoted for other recent navigation series [3], [7], [17]. In our institution, with the use of navigation routinely, operation times appear to still be within the range that would be expected for non-navigated surgery.…”
Section: Discussionsupporting
confidence: 85%
“…Although it has been shown that image-free computer-navigated total knee arthroplasty (TKA) improves component positioning and overall lower limb alignment [1], [2], [3], [4], it has not been widely adopted. This is due to a number of criticisms including that it increases operation times and the risks of problems with the tracker bone screw insertion sites [1], [5], [6], [7], [8], [9], [10], [11].…”
Section: Introductionmentioning
confidence: 99%
“…reported that varus lower limb alignment after TKA resulted in poor self-reported clinical outcomes using the New KSS. Gothesen et al [24]. reported that TKA using CAS achieved better alignment and clinical alignment than conventional technique.…”
Section: Discussionmentioning
confidence: 99%
“…31 More recent studies have begun to show some evidence of functional efficacy including KOOS (Knee Injury and Osteoarthritis Outcome Score) scores at one year over conventional techniques, as well as a consistent demonstration of improved component and limb alignments known to be important in long term component survival. 32 Thus it is hoped that computer navigation, by leading to higher proportions of accurately aligned knee prostheses, including sizing and rotations, will lead to increased longevity and improved function, but this will remain unproven until long term clinical outcomes of CASN assisted TKR's can be correlated with detailed analysis of intra-operative events.…”
Section: Results and Benefit Analysis Of Computer Assistance In Tkrmentioning
confidence: 99%